Effects of multiple spark ignition on engine knock under different compression ratio and fuel octane number conditions. (15th February 2022) - Shi, Hao; Tang, Qinglong; Uddeen, Kalim; Johansson, Bengt; Turner, James; Magnotti, Gaetano
Highlights: Using multiple spark ignition to generate controlled knock and different knock mechanisms. Uncovering the non-monotonic knock behavior with adding more spark ignition sites. The knock intensity is determined by the dual effects of end-gas temperature and mass fraction. Investigating the CR and fuel ON effects on the potential knock mitigation with four spark ignition. The rebuilt 2D knock vibration plots based on six pressure sensors show high consistency with FFT results. Abstract: Engine knock has long been one of the major obstacles for improving thermal efficiency of spark-ignition (SI) engines. An in-depth understanding of the engine knock mechanism and characteristics is vital for controlling knocking combustion. Experimental investigation of knock events is challenging given their stochastic nature. We employ a single-cylinder research engine equipped with a specialized metal liner with four circumferentially mounted spark plugs to generate multiple ignition sites, and achieve more controlled knock events. Six pressure transducers are mounted to collect the pressure signals from different locations of the cylinder. A series of spark strategies (e.g., spark number, location and timing) are applied to investigate the knock characteristics of different spark ignition strategies. The effects of compression ratio and fuel octane number are also explored. The experimental results show that the knock intensity first increases as the number of active sparks goes from one to three and decreases significantly with four spark ignition, and even below the double spark ignition in some cases. This is due to the trade-off between the mass fraction and temperature of end-gas: nearly 90% of the fuel energy is consumed at knock onset in the four spark ignition cases, and only a small proportion of energy is consumed by auto-ignition, thus limiting the knock intensity. Compared with the single spark case, multiple spark ignition generates higher power output and lower cycle-to-cycle variations. The knock suppressing effect of the four spark ignition strategy is enhanced by higher fuel octane number and lower compression ratio. This study provides a possible way to generate controllable knock and gives insights into the different knock mechanisms under multiple spark ignition conditions.